Do high impact exercises produce higher tibial strains than running?. Issue 3 (1st June 2000) - Milgrom, Charles; Finestone, Aharon; Levi, Yael; Simkin, Ariel; Ekenman, Ingrid; Mendelson, Stephen; Millgram, Michael; Nyska, Meir; Benjuya, Nissim; Burr, David
Abstract : Background —Bone must have sufficient strength to withstand both instantaneous forces and lower repetitive forces. Repetitive loading, especially when bone strain and/or strain rates are high, can create microdamage and result in stress fracture Aim —To measure in vivo strains and strain rates in human tibia during high impact and moderate impact exercises. Methods —Three strain gauged bone staples were mounted percutaneously in a rosette pattern in the mid diaphysis of the medial tibia in six normal subjects, and in vivo tibial strains were measured during running at 17 km/h and drop jumping from heights of 26, 39, and 52 cm. Results —Complete data for all three drop jumps were obtained for four of the six subjects. No statistically significant differences were found in compression, tension, or shear strains with increasing drop jump height, but, at the 52 cm height, shear strain rate was reduced by one third (p = 0.03). No relation was found between peak compression strain and calculated drop jump energy, indicating that subjects were able to dissipate part of the potential energy of successively higher drop jumps by increasing the range of motion of their knee and ankle joints and not transmitting the energy to their tibia. No statistically significant differences were found between the principal strains during running and drop jumping from 52 cm, but compression (p = 0.01) and tension (p = 0.004) strain rates were significantly higher during running. Conclusions —High impact exercises, as represented by drop jumping in this experiment, do not cause higher tibial strains and strain rates than running and therefore are unlikely to place an athlete who is accustomed to fast running at higher risk for bone fatigue.